The Interrelationship between Room Acoustics Parameters as Measured in University Classrooms Using Four Source Configurations. Issue 1 (March 2013) - Nestoras, Christos; Dance, Stephen
This paper investigates the interrelation of room acoustics parameters as measured in lecture theatres/classrooms using four sound source configurations. Ten typical rooms were selected as representative of university premises and measured to ISO 3382 standards. The study focuses initially on the type of sound source used, to establish the suitability of multi source based measurements in assessing the acoustics of classrooms. Acoustic performance is then discussed in the context of the relationship between room acoustics parameters with and without significant background noise, with a particular focus on speech intelligibility. To facilitate a more efficient discernment of results, EDT, T30, Clarity indices and MTI were considered, as they are commonly included in general room acoustics assessments. Either of the source configurations was found to be suitable for performing general purpose measurements in (small) rooms. Clarity and EDT were found to be linearly related to the modulation transfer index in noiseless conditions, in line with earlier findings, thus an excellent predictor of STI. Background noise could be ascertained as of primary importance in the case of a non linear relation.